Use of free Wi-Fi to better understand food and people flow in markets in Hanoi - CGIAR Platform for Big Data in Agriculture (2019)
During the first year, we provided Internet through Wi-Fi within 5 markets in Hanoi and to use this system to monitor food and people flows in the markets. This phase clearly demonstrates the feasibility of using free Wi-Fi to better understand food and people flows in markets